The Use of Manajemen Nutrisi Balita Stunting (MNBS) Smartphone Application as an Educational Media on Maternal Knowledge and Attitudes in Preventing Stunting in Geneng District Ngawi Regency - Kurniawan Erman Wicaksono; Sena Wahyu Purwanza; Ika Arum Dewi Satiti; Ida Nurmawati; Ikha Nurjihan (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Stunting indicates a high prevalence of nutritional deficiencies that have not yet reached reduction targets, as seen in Geneng District, Ngawi Regency. Maternal knowledge and attitudes are crucial factors in preventing stunting and can influence mothers' behaviors in ensuring nutrition for toddlers. Manajemen Nutrisi Balita Stunting (MNBS) is an innovative intervention designed to address specific nutritional needs. It was developed into a smartphone application that serves as an educational tool to prevent stunting issues. This study aims to analyze the impact of MNBS on maternal knowledge and attitudes towards stunting prevention. This study used a one-group pretest-post-test design approach. Sampling was conducted using simple random sampling involving 30 respondents. Inclusion criteria for this research included mothers with toddlers experiencing malnutrition, owning a smartphone, and being willing to participate in the study until completion. The research results indicate that maternal knowledge and attitudes towards preventing stunting improved after receiving education through Manajemen Nutrisi Balita Stunting (MNBS) smartphone application. Manajemen Nutrisi Balita Stunting (MNBS) Smartphone Application has an impact as an educational medium on maternal knowledge and attitudes toward preventing stunting.